PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL DIMODERASI OLEH KOMITMEN ORGANISASI PADA PT. KHARISMA ASTRA NUSANTARA DI JAKARTA - Mustaji Burokhman (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2017)
This research is a study on "The Effects of Budgetary Participation and Management Accounting System Against The Managerial Performance Moderated By Organizational Commitment At PT. Astra Kharisma Nusantara in Jakarta ". The dependent variable in this study is the Managerial Performance, while the independent variable is the participation of Budgeting and Accounting Management System. Moderating variables using variable Organizational Commitment. The population was manager at PT. Aastra Kharisma Nusantara in Jakarta. Samples that meet the criteria are as many as 35 managers. The study was conducted by a couple of stages. The first stage is to explore the theory of literature to determine the formulation of research problems and hypotheses. The second stage is the collection of data from the unit of analysis is researched. The third stage is to test the feasibility of using the data validity and reliability. The fourth stage is the stage of the research hypothesis testing using multiple regression to test the hypothesis either partially or simultaneously. Fifth stage is testing the impact of Organizational Commitment moderation, strengthen or weaken the effect of variable Participation Budgeting and Management Accounting Systems on Managerial Performance. The results of this study prove that partially, Budgetary Participation variables no significant effect on Managerial Performance, while the Management Accounting System variables significantly influence managerial performance. Participation variables simultaneously Budgeting and Accounting System Management Managerial significant effect on performance. Moderation Organizational Commitment able to strengthen the influence of the Effect of Budgetary Participation and Management Accounting Systems on Managerial Performance.